Duplex PCR for Detection of Aleutian Disease Virus from Biological and Environmental Samples - Kowalczyk Marek (Sciendo, 2019)
Aleutian disease is one of the most serious disease entities affecting mink farms. The disease causes significant economic losses in mink breeding countries. The aim of the study was to optimize a diagnostic test based on duplex PCR to enable detection of Aleutian disease virus in biological and environmental samples.